Sposoby i formy zawarcia ugody mediacyjnej w dobie pandemii COVID-19 - Arkuszewska, Aneta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Przedmiotem artykułu jest przedstawienie sposobów zawarcia ugody mediacyjnej w dobie pandemii COVID-19 w sytuacji prowadzenia mediacji online, co wiąże się z zastosowaniem odpowiedniej formy, tj. pisemnej lub elektronicznej. Wskazano, że w związku z pandemią pojawiała się nie tyle nowa forma, ale nowatorski sposób jej zawarcia – w trybie art. 183 12 § 2 in fine k.p.c., który jest dopuszczalny przez sąd, jednak powinien być stosowany tylko wyjątkowo i tylko wówczas, gdy sąd upoważni mediatora do takiego sposobu zawarcia ugody, aby mogła ona wywołać wszystkie skutki w sferze prawa materialnego oraz procesowego.

The purpose of this paper is to present the methods of concluding mediation agreements in the era of the COVID-19 pandemic in the situation of online mediation, which involves the use of an appropriate form, i.e. written or electronic. It has been pointed out that in connection with the pandemic it is not so much the new form but an innovative way of concluding a mediation agreement, i.e. by means of Art. 183 12 § 2 in fine of the Civil Procedure Code, which is admissible by the court but should be used only exceptionally and only when the court authorizes the mediator to conclude an agreement in such a way that it can have all the effects in the sphere of substantive and procedural law.
Keywords: ugoda mediacyjna; forma ugody; mediacja online; mediation settlement; settlement form; online mediation